THE STUDY OF INVERTEBRATE ZOOLOGY BASED DARTs THROUGH LESSON STUDY AS AN EFFORT IN BUILDING THE BIOLOGY STUDENTS?óÔé¼Ôäó CRITICAL THINKING - Eny Hartadiyati W. H.; Maria Ulfah; Praptining Rahayy (Universitas PGRI Semarang, 2013)
Activity lesson study is one means for faculty to enhance professionalism in the learning activities. Through lesson study activity which consists of three stages: plan, do and see, teachers can enhance learning systematically, and can build pedagogical knowledge. This study aims to develop an invertebrate zoology course in learning biology using model based learning DARTs (Directed Activities Related to Texts), or activities which are directed to read the text or reading. Through learning-based invertebrate zoology DARTs expected to increase students' critical thinking skills and create effective learning.Learning-based invertebrate zoology Darts begins by compiling Student Worksheet together with lesson study teams, then the Student Worksheet to classroom study tested twice.The model of Invertebrate zoology learning best on DARTs through Lesson Study can helped teacher to develop Students work sheet. This can be seen in the increase in observations of students is increasing. Critical thinking skills can help students to understand the material presented so that invertebrate zoology student understanding can be fully or thoroughly.Keywords: Learning Development Invertebrate Zoology, DARTs (Directed Activities Related to Texts), Lesson Study.